A Novel 3D Visualized Operative Procedure in the Single-Stage Complete Repair With Unifocalization of Pulmonary Atresia With Ventricular Septal Defect and Major Aortopulmonary Collateral Arteries - Qiu, Hailong; Wen, Shusheng; Ji, Erchao; Chen, Tianyu; Liu, Xiaobing; Li, Xiaohua; Teng, Yun; Zhang, Yong; Liufu, Rong; Zhang, Jiawei; Xu, Xiaowei; Chen, Jimei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries (PA/VSD/MAPCAs) is a relatively rare, complex and heterogeneous congenital heart disease. As one of the effective treatments, the midline unifocalization strategy still remains complicated and challenging due to the diverse forms of MAPCAs and pulmonary arteries. The purpose of this paper is to summarize our experience of the novel three-dimensional (3D) visualized operative procedure in the single-stage complete repair with the unifocalization operation and to clarify the benefits it may bring to us. Methods: We described our experience of the 3D visualized operative procedure including 3D printing, virtual reality (VR) and mixed reality (MR) technology in PA/VSD/MAPCAs patients undergoing the single-stage complete repair with unifocalization. The data of the patients following this procedure (3D group) and the ones following the conventional procedure (conventional group) were compared. Results: The conventional and 3D groups included 11 patients from September 2011 to December 2017 and 9 ones from January 2018 to March 2021, respectively. The baseline Characteristics including the age, body weight, preoperative saturation, the anatomy of the pulmonary arteries and MAPCAs, Nakata index and TNPAI had no statistical significance. All the 9 patients in the 3D group were operated only through a median sternotomy, while 8 cases (72.7%) needed another posterolateral thoracotomy in the conventional group (p=0.001). In the 3D group, the CPB time was shorter (93.2±63.8 vs 145.1±68.4 min, p=0.099), and the median pre-CPB time per MAPCAs was significantly shorter (25.7 [14.0,46.3] vs 65 [41.3,75.0] min, p=0.031). There was no early death in the 3D group, while there were 3 in the conventional group (0 vs 27.3 %, p=0.218) Conclusion: The novel 3D visualized operative procedure may contribute to the better performance of the single-stage complete repair with the midline unifocalization of PA/VSD/MAPCAs and help shorten the dissecting time of the MAPCAs. It may promote the routine and successful application of this strategy in more centers.